Activation of selected core muscles during squatting - Nesser, T. W.; Fleming, N.; Gage, M. J. (Journal of Athletic Enhancement, 2016)
Purpose of this study was to determine core muscle activation during ground-based lifts. Fourteen recreational trained and former NCAA DI athletes (weight 84.2 ± 13.3 kg; height 176.0 ± 9.5 cm; age 20.9 ± 2.0 years) volunteered for participation. Subjects completed two ground-based lifts: overhead press and push-press. Surface EMG was recorded from 4 muscles on the right side of the body; Rectus Abdominus (RA), External Oblique (EO), Transverse Abdominus (TA) and Erector Spinae (ES). Paired sample T-tests identified significant muscle activation differences between the overhead press and the push-press included ES and EO. Average and peak EMG for ES was significantly greater in push-press (P<0.01). Anterior displacement of COP was significantly greater in push-press compared to overhead press during the eccentric phase. The push-press was identified as superior in core muscle activation when compared to the overhead press